Three new species of the Rhyacophila retracta species group (Trichoptera, Rhyacophilidae) from Japan - Kawase, Naoki (Zootaxa, 2025)
Three new species of the Rhyacophila retracta Species Group Ross 1956 are described from Japan: R. geranos sp. nov., R. humerigera sp. nov. and R. koryne sp. nov. Adult males and females of the three new species are described and illustrated. Illustrations of male and female genitalia of four previously known species belonging to this species group, R. retracta Martynov 1914, R. motakanta Schmid 1970, R. lambakanta Schmid 1970, and R. orthacantha Emoto 1979, are provided for comparisons. Distribution maps for all seven species are presented.